Pencapaian Hasil Belajar Biologi dengan Model Problem Based Learning (PBL) dan Model Kooperatif Tipe Student Teams-Achievement Divisions (STAD) Ditinjau dari Minat Belajar Peserta Didik Sekolah Menengah Atas Negeri di Kabupaten Grobogan - Ririk Niangkasawati; Mulyoto Mulyoto; Deny Tri Ardianto (Teknodika, 2016)
The objectives of this research are to investigate: (1) the difference of effect between the PBL model and the cooperative learning model of the STAD type on the Biology learning outcome of the students of Senior Secondary Schools of Grobogan Regency; (2) the difference of effect between the high learning interest and the low learning interest on the  Biology learning outcome of the students of Senior Secondary Schools of Grobogan Regency; (3) and the interaction of effect between the learning models and the learning interests on the Biology learning outcome of the students of Senior Secondary Schools of Grobogan Regency. This research used the experimental research method with the factorial design of 2x2. It was conducted at Senior Secondary Schools of Grobogan Regency. The results of this research are as follows: (1) there was a significant difference of effect between the PBL model and the cooperative learning model of the STAD type on the Biology learning outcome of the students of Senior Secondary Schools of Grobogan Regency where the former had a better effect on the Biology learning outcome than the latter as indicated by the result of the two-way analysis of variance (ANOVA) in which the F-value  was 4.669 and the p-value was smaller than 0.05; (2) there was a significant difference of effect between the high learning interest and the low learning interest on the Biology learning outcome of the students of Senior Secondary Schools of Grobogan Regency where the former had a better effect on the Biology learning outcome than the latter as indicated by the result of the twoway analysis of variance (ANOVA) in which the F-value  was 5.554 and the p-value was smaller than 0.05; and (3) there was an interaction of effect between the learning models and the learning interests on the Biology learning outcome of the students of Senior Secondary Schools of Grobogan Regency as indicated by the result of the two-way analysis of variance (ANOVA) in which the F-value was 4.434, and the p-value was smaller than 0.05. The highest average score in Biology learning of the students with the PBL model and with the high leaning interest was 83.88, whereas the lowest score in Biology learning of the students with the PBL model and with the low learning interest was 74. 47